(untitled) (Glocalism: Journal of Culture, Politics and Innovation, 2022)
In Silicon Valley, new technology is considered to be second nature. Techies from all over the world go there to develop companies, solutions or projects related to it. To do this, they need to manage two processes simultaneously: first, to integrate a growing flow of entrants and possible partners and, secondly, to select limited options between multiple opportunities and potential matches. This article analyzes the way Silicon Valley professionals handle this double bind. Based on a survey in the region and conceptual tools inherited from the sociology of globalization, it sheds light on how they build up, use and communicate about “culture” as a measurable and assessable variable. On the one hand, promotion of Silicon Valley’s “culture codes” increases the flow of entrants. On the other hand, from the techies’ point of view, acceptance of these codes by newcomers makes the selection process easier and more rational.